Plexiform tumorlet in a woman with postmenopausal endometrioid endometrial carcinoma taking tamoxifen for breast cancer: A case report - Nektarios Koufopoulos; Ioannis Boutas; Dionysios Dimas; Adamantia Kontogeorgi; Constantine Dimitrakakis (Elsevier, 2022)
Leiomyomas are the most common benign smooth muscle tumors of the female genital tract. Among the recognized histologic variants, one of the least common is plexiform leiomyoma. When they are small, even microscopic findings, they are referred to as plexiform tumorlets.In this report the authors describe a case of plexiform tumorlet found incidentally in the hysterectomy specimen of a 64-year-old woman with concomitant endometrioid endometrial carcinoma and a previous history of invasive lobular breast carcinoma. The endometrioid endometrial carcinoma arising on a polyps was diagnosed in a curettage specimen. In the hysterectomy specimen there was no residual endometrioid endometrial carcinoma. Six uterine leiomyomas were found. A small (3 mm) well circumscribed tumor was located in the uterine wall. Histologically it consisted of small nests, islands, cords, and tubules of relatively uniform, round to oval cells surrounded by loose stroma. The differential diagnosis was challenging, and included plexiform leiomyoma, uterine tumor resembling ovarian sex cord tumor, endometrial stromal tumor, and poorly differentiated endometrial or metastatic invasive lobular breast carcinoma. After careful morphologic evaluation and appropriate use of immunohistochemical stains the diagnosis of plexiform tumorlet was made.